Co-spray dried carbohydrate microparticles: crystallisation delay/inhibition and improved aerosolization characteristics through the incorporation of hydroxypropyl-?-cyclodextrin with amorphous raffinose or trehalose - TAJBER, LIDIA; HEALY, ANNE (My University, 2015)
PURPOSE: To formulate and investigate the physicochemical properties, physical stability and aerosolization characteristics of nanoporous/nanoparticulate microparticles (NPMPs) prepared by co-spray drying the sugars raffinose pentahydrate (R) or trehalose dihydrate (T) with the cyclic oligosaccharide hydroxypropyl-β-cyclodextrin (HPβCD). METHODS: Production of powders was carried out using a laboratory scale spray dryer. The resulting powders were characterised by X-ray powder diffraction (XRPD), scanning electron microscopy (SEM), laser diffraction particle sizing, specific surface area analysis (SSA), Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), dynamic vapour sorption (DVS) and aerodynamic assessment using a Next Generation Impactor (NGI). RESULTS: Powders were amorphous and composed of spherical, porous microparticles with reduced particle size and high specific surface area (~100 m2/g). DSC scans showed a single glass transition temperature. FTIR was indicative of the existence of molecular interactions between the carbohydrates. DVS analysis showed an increase in the critical relative humidity (RH) of raffinose and trehalose and eventual crystallization inhibition with increasing concentration of HPβCD. The in vitro deposition showed powders formulated with HPβCD had higher recovered emitted dose and fine particle fraction (<5 μm) than raffinose and trehalose spray dried alone. CONCLUSIONS: The co-spray drying of raffinose or trehalose with HPβCD results in powders with improved physicochemical characteristics, physical stability and aerodynamic behaviour compared to spray-dried raffinose/trehalose particles, constituting improved potential drug-carrier systems for pulmonary delivery.
PUBLISHED
Keywords: Aerosol; Nanoscience & Materials; Drug development and evaluation